The Role of Bacterial Lysates in Improving Physical Performance in Patients with Respiratory Tract Infections and Chronic Obstructive Pulmonary Disease - Kolasa, Wiktoria; Szeliga, Katarzyna; Kolanko, Magdalena; Stołecka, Greta; Grabowska, Julia; Korzeniowska, Anna; Mikółka, Karolina; Jędrysiak, Joanna; Lelonkiewicz, Martyna; Kosidło, Patrycja (Quality in Sport, 2026)
Background. Respiratory tract infections (RTIs) represent a major clinical burden and are a common cause of antibiotic use and healthcare utilization. In patients with chronic obstructive pulmonary disease (COPD) respiratory infections are a leading trigger of acute exacerbations, contributing to disease progression and increased morbidity. Bacterial lysates (BLs) have emerged as immunomodulatory agents aimed at enhancing host immune responses and reducing infection recurrence. The aim of this article is to expand knowledge about the beneficial impact of BLs in the prevention of RTIs and in the management of COPD. Aim. This review aimed to analyze current evidence on the effects of bacterial lysates on RTIs and COPD. Material and methods. The narrative review of the literature was conducted using databases including PubMed, Google Scholar and MEDLINE. The search was limited to articles published in English from 2020 onwards. Studies were selected based on clinical relevance and applicability to adult patients with RTIs and COPD. This article focuses on recent clinical studies, reviews, meta-analyses and guidelines (GOLD, ERS). Results. Existing clinical evidence and guideline recommendations suggest that BLs may serve as a valuable adjunct to standard preventive and therapeutic strategies in RTIs and COPD. They may reduce the frequency and severity of respiratory tract infections. In patients with COPD, bacterial lysates may help decrease the rate of COPD exacerbations and improve disease control. Conclusions. BLs represent a promising immunomodulatory strategy in the prevention and management of RTIs and COPD. Although current data are encouraging, heterogeneity among studies highlights the need for further large-scale, well-designed randomized controlled trials.